ANALISIS PENGUNGKAPAN INTERNET FINANCIAL REPORTING PADA PERUSAHAAN SUBSEKTOR FARMASI DI INDONESIA - Desyria Pratiwi (Institut Bisnis Muhammadiyah Bekasi, 2023)
Disclosure of Internet Financial Reporting (IFR) makes it easy for users or interested parties to find financial information through the company's official website. This study aims to reveal the effect of profitability, leverage, and company size on Internet Financial reporting disclosure in the pharmaceutical subsector in Indonesia. The population of this research is all pharmaceutical sub-sector companies that are on the Indonesia Stock Exchange until 2021. The sampling technique used in this study is using the Purposive Sampling method with an observation period from 2019 to 2021. The sample data is then analyzed using multiple linear regression analysis using SPSS 27.0. The results of the analysis of this study are that the Leverage and Firm Size variables influence IFR, while the Profitability variable does not influence IFR. Meanwhile, the independent variables used in the study simultaneously affect IFR.